REKAYASA KONSUMSI, DIFERENSIASI SOSIAL, DAN KOMUNIKASI - Fardiyan, Ahmad Rudy (JURNAL SOSIOLOGI, 2012)
This research investigating social consumption behavior in critical perspective. Consumption behavior could be said as a factor which describe social economics level. However, this research focused on socio-culturalÂ problems related to consumption behavior, by using inspecting literature methods. This research revealed that consumption behavior can create social differentiation. Consumption then could be says as communication activity.Â Keywords: consumption, commodity, sign-value